Extraction of Forest Products in Mount Kenya Forest, Kenya; Linking Household Characteristics to Participation - Anderson Kipkoech; Mwangi Flora Caroline; Ernest Saina; Samuel Mwakubo; Samuel Otieno John (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2026)
This study analysed the socio-economic and environmental factors influencing household participation in the extraction of forest products from Mount Kenya Forest, Kenya. The methodology A cross-sectional survey design was employed to gather quantitative data on household-level participation in forest product extraction. This design was selected for its cost-effectiveness and suitability for capturing data at a single point in time. A multistage sampling approach was adopted to identify sampling units.. Descriptive analysis shows that 77% of households participated in forest product extraction, primarily for domestic and commercial purposes, only 361 respondents were captured and found suitable for this study. The results reveal that household size, income, education level, awareness of forest management practices, and distance to the forest significantly influence participation. The binary logistic regression analyses confirmed these factors as key determinants, with larger households and lower education correlating positively with higher extraction rates for products like firewood, medicinal plants, and fodder, while wealthier and employed individuals showed reduced dependency. These results confirm that forest resource use is multifactorial, driven by a blend of necessity, opportunity, and awareness. They also highlight that forest degradation is not solely a function of a single factor but rather is influenced by household strategies to meet diverse livelihood needs.